Medical student training with next-generation handheld ultrasound devices – hands on examination of fetal biometry in obstetrics - Ruben Plöger; Julia Matschl; Adeline Walter; Ulrich Gembruch; Brigitte Strizek; Charlotte Behning; Agnes Wittek; Florian Recker (BMC Medical Education)
Abstract Introduction The technical development of ultrasound devices based on silicon chips has revolutionized ultrasound examinations, leading to the implementation of these portable handheld devices (PUD) in different medical fields. However, training on these devices is necessary to assure appropriate use and ensure valid results. While training programs for the use of conventional standard ultrasound devices (SUD) have been described, no training program for these handheld devices has been developed thus far. Methods A training program for obstetric ultrasound examination was modified through the addition of an extra module focusing on the use of these PUDs. After the module the students had to attend an OSCE in which their skills of using the PUD and the SUD were tested and analyzed by applying the agreement rate, the intraclass correlation coefficient (ICC) and Bland–Altman plots. Furthermore, the students’ ultrasound results were compared with those of trained physicians by employing the one-sample Student's t-test. After the OSCE, the students answered a survey regarding their experience and their expected use of these devices. Result An agreement of one hundred percent was reached for basic parameters such as fetal position, placental position, fetal heartbeat and for the classification of the amniotic fluid. The ICC showed a good to moderate agreement between the results of fetal biometry achieved by SUD and PUD. The T-test results confirmed a high reliability between the physicians’ results and the students’ results, independent of the used device. The students remarked a good handling of the ultrasound devices and supported the use in their future specialties. Discussion The reliability between the examinations using the SUD and PUD were high but lower than the results observed for trained physicians. Therefore, the implementation of an additional module for portable ultrasound teaches the students to reliably examine basic obstetric parameters and provides a solid basis for further training and improvement of ultrasound skills in use of PUD.